Monitoring ambient air pollutants and apply Woods' model in the prediction seasonal dry deposition at Chang-Hua (urban) and Kao-Mei (wetland) county, Taiwan. (September 2014) - Fang, Guor-Cheng; Chang, Chia-Ying
The main purpose for this study was to monitor ambient air particles and metallic elements (Mn, Fe, Zn, Cr, Cu and Pb) in total suspended particulate (TSP) concentration and dry deposition. In addition, the calculated/measured dry deposition flux ratios of ambient air particles and metallic elements (Mn, Fe, Zn, Cr, Cu and Pb) were evaluated using Woods' model at urban and wetland areas for the 2009–2010 period. The results indicated that the mean highest concentrations of metallic elements Mn, Fe, Zn, Cr, Cu and Pb in TSP were found in Chang-Hua (urban) sampling site. And as for the two characteristic sampling sites, the Woods' model exhibits better dry deposition of particulates of 18 µm particle size than the rest of the other particle sizes at any sampling site in this study. The average calculated/measured flux ratios for two seasons (summer and fall) by using Woods model at 2.5, 10 and 18 µm particles sizes were also studied. The results indicated that the average calculated/measured flux ratios orders for two seasons of various particles sizes were all displayed as Fe > Mn > Zn > Cu > Cr > Pb > particle. And these calculated/measured flux ratios orders were Fe > Mn > Cu > Zn > Cr > Pb > particle and were Fe > Mn > Zn > Cu > Cr > particle > Pb, during spring and winter seasons, respectively. Finally, in the spring and summer seasons of Gao-Mei (wetland) sampling site, the average calculated/measured flux ratios using Woods' model was found to be 2.5, 10 and 18 µm, showing the order of the calculated/measured flux ratios to be Fe > Cu > Zn > Mn > Cr > Pb > particle. And the calculated/measured flux ratio orders were Fe > Zn > Mn > Cu > Cr > particle > Pb and were Fe > Cu > Zn > Mn > Cr > particle > Pb for fall and winter season, respectively.